The involvement of Argonaute molecule PIWI in the antiviral immunity of oyster Crassostrea gigas - Yuhao Jin; Xue Qiao; Yuqing Zeng; Yiqing Wang; Lilin Hou; Xinyu Zhao; Sicong Wang; Lingling Wang; Linsheng Song (Comparative Immunology Reports)
The p-element induced wimpy testis (PIWI), as a member of Argonaute superfamily, functions in piRNA pathway of RNAi to achieve target gene silencing. The piRNA pathway plays crucial roles in germline development and regulation of mobile element as well as the antiviral immunity. In the present study, a PIWI homologue (CgPIWI) was identified in Crassostrea gigas. The predicted CgPIWI protein consists of a N domain, a PAZ domain, a MID domain and a PIWI domain, and shared identity ranging from 27.04% to 70.37% with other PIWIs. Transcriptome analysis showed that CgPIWI was highly expressed in embryonic period (from egg to blastula stage) and then gradually decreased with the development process (from blastula to early D-larva stage). The mRNA transcripts of CgPIWI were detectable in all the examined tissues of adult oysters with the highest expression in haemocytes. After poly (I:C) stimulation, the mRNA expression level of CgPIWI in haemocytes were significantly increased, particularly in granulocytes of haemocytes. Immunocytochemistry assay revealed that CgPIWI proteins were mainly distributed in the cytoplasm of haemocytes. The recombinant proteins of full-length CgPIWI (rCgPIWI), and its PAZ domain (rCgPIWI-PAZ) and PIWI domain (rCgPIWI-PIWI), were obtained by prokaryotic expression, respectively. Both rCgPIWI and rCgPIWI-PAZ demonstrated significant binding activity to ssRNA in vitro, while no binding activity to dsRNA. Additionally, rCgPIWI and rCgPIWI-PIWI exhibited substantial RNase activity, efficiently cleaving ssRNA in vitro. These results indicated that CgPIWI functions as an effector of RNAi-induced silencing and plays a role in the antiviral immune response of oyster.